1985
DOI: 10.1073/pnas.82.14.4717
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of monoclonal antibodies against Chlamydomonas flagellar dyneins by high-resolution protein blotting.

Abstract: Monoclonal antibodies that recognize individual polypeptides of the outer arm dyneins of Chlamydomonas flagella were obtained and used to study the structural relationships between the various polypeptides. Immunoblot analysis showed that the y heavy chain of 12S dynein and the a and /3 heavy chains and M, 69 The dynein heavy chains migrate very close to one another in NaDodSO4/polyacrylamide gels and are well resolved only at very low protein loadings (2). Consequently, characterization of our antibodies by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(76 citation statements)
references
References 28 publications
(28 reference statements)
1
74
0
1
Order By: Relevance
“…Other antibodies used in this study were blot-purified rabbit polyclonal antibodies R5932 (vs. LC1; Benashski et al, 1999), R5391 (vs. LC2;Patel-King et al, 1997), R4930 (vs. LC3;Patel-King et al, 1996), CT61 (vs. LC4; M. Sakato and King, unpublished data), R4929 (vs. LC5;Patel-King et al, 1996), R4928 (vs. LC6; King and Patel-King, 1995), R7178 (vs. LC7a;Bowman et al, 1999), CT116 (vs. LC7b;DiBella et al, 2004a), R4058 (vs. LC8; King and Patel-King, 1995), and anti-DC 2 (Wakabayashi et al, 2001), and mouse monoclonal antibodies 12␥B (vs. ␥ HC; King et al, 1985), 1878A (vs. IC1; King et al, 1986), and 1869A (vs. IC2; King et al, 1985). Antibody reactivity was detected using peroxidase-conjugated secondary antibodies and an enhanced chemiluminescent substrate (GE Healthcare, Little Chalfont, Buckinghamshire, United Kingdom).…”
Section: Preparation Of Fusion Proteins and Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other antibodies used in this study were blot-purified rabbit polyclonal antibodies R5932 (vs. LC1; Benashski et al, 1999), R5391 (vs. LC2;Patel-King et al, 1997), R4930 (vs. LC3;Patel-King et al, 1996), CT61 (vs. LC4; M. Sakato and King, unpublished data), R4929 (vs. LC5;Patel-King et al, 1996), R4928 (vs. LC6; King and Patel-King, 1995), R7178 (vs. LC7a;Bowman et al, 1999), CT116 (vs. LC7b;DiBella et al, 2004a), R4058 (vs. LC8; King and Patel-King, 1995), and anti-DC 2 (Wakabayashi et al, 2001), and mouse monoclonal antibodies 12␥B (vs. ␥ HC; King et al, 1985), 1878A (vs. IC1; King et al, 1986), and 1869A (vs. IC2; King et al, 1985). Antibody reactivity was detected using peroxidase-conjugated secondary antibodies and an enhanced chemiluminescent substrate (GE Healthcare, Little Chalfont, Buckinghamshire, United Kingdom).…”
Section: Preparation Of Fusion Proteins and Antibodiesmentioning
confidence: 99%
“…Previously, we observed that both IC1 and IC2 yielded products of M r 82,000 and 91,000, respectively, after EDC treatment (King et al, 1991;DiBella et al, 2004a), and the M r of these LC9-containing products suggested that they may derive from attachment of LC9 to both IC1 (76,623 Da) and IC2 (63,519 Da). To test whether these bands indeed represent LC9-IC complexes, blots of dynein samples treated with 20 mM EDC were cut lengthwise and one-half probed with CT231 and the other with either 1878A (vs. IC1; King et al, 1986) or 1869A (vs. IC2; King et al, 1985) (Figure 4, middle and right). After reassembly of the blots, we found that the lower and upper LC9-containing bands precisely comigrated with bands detected by 1869A and 1878A, respectively.…”
Section: Lc9 Interacts Directly With Ic1 and Ic2mentioning
confidence: 99%
“…Oda5p was localized using the anti-Oda5p antibody diluted 1:1000 in 5% horse serum in 1ϫ Tris-buffered saline/0.5% Tween 20. IC2, the ␥DHC, DC2, and IC140 were revealed using monoclonal antibodies 1869A and 12␥B (King et al, 1985), an anti-DC62 polyclonal antibody (Wakabayashi et al, 2001), and an anti-IC140 polyclonal antibody (Yang and Sale, 1998), respectively. Horseradish peroxidase-conjugated secondary antibodies (Pierce Chemical, Rockford, IL; Sigma-Aldrich) were used at 1:2000.…”
Section: Western Blotsmentioning
confidence: 99%
“…24. For Western blot analysis (25) proteins were transferred onto a nitrocellulose membrane using a semi-dry blotting apparatus by applying 50 mA/gel for 1 h at 4°C. After transfer, the membrane was blocked overnight in phosphate-buffered saline buffer containing 3% (w/v) BSA, 0.1% (w/v) Triton X-100.…”
Section: Separation and Isolation Of Nhaa Tryptic Fragments And Determentioning
confidence: 99%